2019
DOI: 10.1016/s2215-0366(19)30030-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of future suicide attempt among adolescents with suicidal thoughts or non-suicidal self-harm: a population-based birth cohort study

Abstract: Summary Background Suicidal thoughts and non-suicidal self-harm are common in adolescents and are strongly associated with suicide attempts. We aimed to identify predictors of future suicide attempts in these high-risk groups. Methods Participants were from the Avon Longitudinal Study of Parents and Children, a population-based birth cohort study in the UK. The sample included 456 adolescents who reported suicidal thoughts and 569 who reported non-suicidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
201
1
13

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(253 citation statements)
references
References 44 publications
(67 reference statements)
24
201
1
13
Order By: Relevance
“…Second, several factors in our analysis clearly discriminated between those who ideate and attempt suicide in a multivariate context. Notably, NSSI conferred a three-fold increased risk of suicide attempt among prisoners with suicidal ideation, which adds to an extensive body of literature documenting that NSSI robustly predicts the progression from suicidal ideation to attempt among youth (Georgiades et al, 2019;Kiekens et al, 2018;Mars et al, 2019b;Taliaferro and Muehlenkamp, 2014). We found that over two-thirds (69%) of the prisoners who reported both suicidal ideation and NSSI had attempted suicide, which compares with only 1% of those who did not report either of these.…”
Section: Discussionmentioning
confidence: 52%
“…Second, several factors in our analysis clearly discriminated between those who ideate and attempt suicide in a multivariate context. Notably, NSSI conferred a three-fold increased risk of suicide attempt among prisoners with suicidal ideation, which adds to an extensive body of literature documenting that NSSI robustly predicts the progression from suicidal ideation to attempt among youth (Georgiades et al, 2019;Kiekens et al, 2018;Mars et al, 2019b;Taliaferro and Muehlenkamp, 2014). We found that over two-thirds (69%) of the prisoners who reported both suicidal ideation and NSSI had attempted suicide, which compares with only 1% of those who did not report either of these.…”
Section: Discussionmentioning
confidence: 52%
“…A previous SA is the main risk predictor for future attempts, as well as completed suicides. Therefore, one of the most important interventions in this program was to focus on cases with a history of SB [13], [14] , [15].…”
Section: Follow Up Monitoring Of Suicidal Behaviors Casesmentioning
confidence: 99%
“…Self-harm, defined as "self-injury or self-poisoning irrespective of the apparent purpose of the act" [1,2], first emerges as a significant public health problem during adolescence [3,4]. Evidence suggests that an increasing number of young people are harming themselves [5].…”
Section: Introductionmentioning
confidence: 99%